Factors influencing quality of transnational education: Evidence from a Sino-UK MA program - Zheng, Changqing; Ouyang, Huhua (Frontiers in Psychology, 2023)
With the internationalization of higher education, transnational education (TNE) has gradually become one of the main means to mobility of education resources in many countries. There have been many studies on service quality research, but not many of these studies attempt to directly explore the in-depth factors contributing to service quality. This study investigated the factors impacting the quality of TNE based on the interpretation of students’ experiences on a Sino-UK MA program. Semi-structured interviews revealed that high-quality educational resources and professional and sympathetic lecturers are the two major factors impacting the service quality. The results suggested that educational resources that meet the local social needs are considered desirable service offerings. Lecturers are key factors guaranteeing the service delivery. This study sheds light on service quality components of TNE that have not been given much attention in the literature of previous research, as well as informs host and export institutions on TNE programming.